PERSEPSI KELUARGA PASIEN TERHADAP PERILAKU CARING PERAWAT RUANG ICU RSUD KECAMATAN MANDAU - Yuliyanti " "; Veny " Elita; Arneliwati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Caring is an interpersonal relationship between nurse and patient in providing nursing care. The ICU nurses must have a caring attitude to provide quality nursing care so that patient and family satisfaction can be achieved.This study aims to determine the patient's family perceptions about the behavior of the nurses caring Mandau District Hospital ICU waiting room 2016. The design is descriptive with survey techniques, in which the data collection is done by using a questionnaire. The analysis is univariate analysis. The results showed that 21 out of 30 respondents (70%) have the perception  that  the ICU nurses have good behaviour and 9 respondents (30%) have a poor perception. Suggestion, based on the result it is suggested  to nurses increase nursing care by constantly reminding among nurses while performing nursing care.Keywords: Caring, Families Patients, Nurses and Family Perception